Risk Factors for Dyspepsia Incidence in Community Aged 15-64 Years in Oesao Village, Oeaso Community Health Center Work Area - Ndun, Elistho Adrianus; Purnawan, Sigit; Sakke Tira, Deviarbi (Universitas Nahdlatul Ulama Surabaya, 2024)
Dyspepsia is a non-communicable disease affecting the digestive system, characterized by symptoms such as heartburn, abdominal discomfort, nausea, vomiting, bloating, and feeling of fullness. As of June 2022, more than 376 cases of dyspepsia were reported in the village of Oesao, with the condition being most prevalent among individuals aged 15-64 years. This study aimed to identify the risk factors for dyspepsia in individuals aged 15-64 in the village of Oesao and its surrounding areas, served by Puskesmas Oesao. An analytic observational study with a case-control design was conducted at Puskesmas Oesao from May to June 2023. A total of 213 respondents were recruited using random sampling with a 1:2 ratio. Data was collected through interviews. The relationship between various factors and dyspepsia incidence was analyzed using p- values with alpha <0.05 as the significance threshold. The results of the study showed that diet was significantly associated with dyspepsia (p < 0.05). Coffee consumption was significantly associated with dyspepsia (p < 0.05). Alcohol consumption was significantly associated with dyspepsia (p < 0.05). Sour and spicy foods were significantly associated with dyspepsia (p < 0.05). This study concludes that coffee, alcohol, sour, and spicy foods have a significant relationship with the incidence of dyspepsia.